EXPERIENCIA DE REGENERACIÓN DE ENCINAR EN LA SIERRA DE HUELVA Studies on holm oak regeneration in North Sevilla mountains - Porras Tejeiro, C J; Brun Esquiliche, P; Copete Gutiérrez, J; Pérez Méndez, R (Cuad. Soc. Esp. Cien. For Actas de la III Reunión sobre Repoblaciones Forestales, 2004)
We have described an oak regeneration research without prohibit the grazing. Three implantation types and seven protections types have been tested. Several parameters have been measured to the seven, fifteen and twenty three months since the seeding or planting
Keywords: Dehesa; Grazing; implantación; Implantation; pastoreo; protección; Protection; Quercus